A design and preparation method for Yellow River sand flood control stone based on water film thickness and shape correction
Through the design and preparation method of Yellow River sand flood control stone based on the thickness and shape of the water film correction, the problems of scarcity of traditional flood control stone raw materials and environmental pollution are solved, and high-performance, environmentally friendly and economical flood control stone preparation is achieved.
Patent Information
- Application Number
- CN202311461458.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-06
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-11-06
AI Technical Summary
The natural stone is a raw material for traditional flood control stones that is not renewable, resulting in scarcity of stones and rising prices. The existing technology has problems of environmental pollution and resource waste when preparing high-performance flood control stones.
The design and preparation method of Yellow River sand flood control stone based on the thickness and shape of water film correction is adopted. Through particle size analysis, the selection of aggregate and gelling materials, the design of bone-gluing ratio and the determination of water usage, the application of close packing theory is achieved.
The prepared flood control stones have high strength and durability, meet the "Planning, Design and Management Standards for Standardized Embankment Projects in the Lower Reaches of the Yellow River", are low in cost, environmental protection, and have high resource utilization. They are suitable for the Yellow River flood control stone embankment projects.
Smart Images

Figure QLYQS_2 
Figure QLYQS_4 
Figure QLYQS_5
Abstract
Description
Technical Field
[0001] The invention relates to a design and preparation method of a Yellow River sand flood control stone based on water film thickness and shape correction, belonging to the technical field of flood control stones. Background Art
[0002] The amount of flood control stones used in the Yellow River rescue work is hundreds of thousands of cubic meters every year. However, natural stone, the raw material of traditional flood control stones, is non-renewable, which has led to a continuous rise in stone prices in recent years. The scarcity of stone has become an urgent problem to be solved in the flood control and rescue work of the Yellow River. According to the annual danger situation of the lower reaches of the Yellow River in recent years, the flood control stone reserves along the Yellow River are far from meeting the rescue needs. Taking Henan as an example, the annual stone reserves for each dam and pile of dangerous engineering and control and guidance projects are only a few hundred cubic meters. Therefore, the development and research of artificial flood control stones is very urgent and necessary.
[0003] Due to the huge demand for artificial flood-control stones, there is a shortage of raw materials, especially aggregates. Yellow River sand is a natural sand with a smooth surface and a small fineness modulus. It can be used to replace normal aggregate to prepare high-performance Yellow River flood-control stones, which has been used in existing technologies.
[0004] In the prior art, the methods of using Yellow River sand to prepare high-strength flood control stones are nothing more than chemical stimulation, load rolling, high-temperature calcination, etc., but these methods often bring about environmental pollution, waste of resources and other problems. Therefore, a method for preparing Yellow River flood control based on the properties of Yellow River sand itself and rationally selecting raw materials is of great significance. Summary of the invention
[0005] The present invention provides a design and preparation method of Yellow River sand flood control stones based on water film thickness and shape correction according to the close packing theory. Firstly, the particle size of the Yellow River sand is analyzed, and then aggregate and cementitious materials are selected based on the analysis results of the Yellow River sand. Then, the aggregate-cement ratio is designed using parameters such as economy and packing density. Finally, the amount of water is determined by calculation and experiment.
[0006] The present invention adopts the following technical solutions:
[0007] A design and preparation method of Yellow River sand flood control stone based on water film thickness and shape correction, comprising the following steps:
[0008] (1) Sorting and drying the Yellow River sand, and analyzing the particle size of the Yellow River sand using a laser particle size analyzer;
[0009] (2) Based on the particle size analysis of aggregates, the shape characteristic parameters are tested, the proportion of aggregates is determined, and the aggregates are mixed and sealed;
[0010] (3) Select the type of cementitious material, modify the particle size, determine the proportion of cementitious materials, mix and seal;
[0011] (4) Determine the bone-gel ratio;
[0012] (5) Determine the water-cement ratio by referring to the specifications and make corrections based on the actual water absorption characteristics of the material to determine the amount of water used;
[0013] (6) Determine the static load pressure F;
[0014] (7) Mix and pour into a mold for shaping and curing.
[0015] Preferably, the process of determining the proportion of aggregate in step (2) is:
[0016] 2.1: Based on the particle size analysis of Yellow River sand, since the particle size distribution of Yellow River sand is concentrated, the particle size with a cumulative pass rate of 50% can be set as r to represent the average particle size of Yellow River sand. The aggregate particle size range is selected to be 1.52r~8.62r. According to the interlayer particle size required by the Horsfield stacking model, the upper and lower interlayer sieve aperture sizes are determined. From top to bottom, the required particle sizes between the layers are 8.62r, 3.57r, 1.94r and 1.52r. The difference in the mesh size of the upper and lower sieves is less than 0.3mm. Since the upper and lower aperture sizes are close, the average particle size of each interlayer particle is calculated according to formula (1):
[0017]
[0018] Where: —average particle size between layers i;
[0019] —The aperture size of the upper screen;
[0020] — Bottom screen aperture size:
[0021] 2.2: Test the roundness and aspect ratio of particles between each layer. Roundness refers to the degree to which particles are close to a circle. The lower the roundness value, the closer the particles are to a circle. When the slump is the same, the lower the shape characteristic parameter, the smaller the interlocking effect between particles, the smaller the porosity of the mixture, and the higher the packing density.
[0022] a i =R×Q (2)
[0023] Where: a i — characteristic parameters of particle shape in layer i;
[0024] R—particle roundness;
[0025] Q—aspect ratio;
[0026] in,
[0027]
[0028] Where: R—particle roundness;
[0029] P—the circumference of the particle under the scanning electron microscope;
[0030] area—the area of the particle projection under the scanning electron microscope;
[0031] The aspect ratio is the ratio of the length and width of the particle diameter. The aspect ratio is:
[0032]
[0033] Where: Q—aspect ratio;
[0034] L—particle length under scanning electron microscope;
[0035] W—particle width under scanning electron microscope;
[0036] When calculating the characteristic parameters of the particles in each layer, the number of particles can be selected to be more than 20, and then the average value is taken as the shape characteristic parameter of the particles in each layer;
[0037] 2.3: Calculate the cumulative passing rate corresponding to the selected particle size by referring to the modified Fuller distribution curve (Formula 5), and determine the dosage of the selected interlayer particles, that is, the proportion of the interlayer particles of the final selected aggregate;
[0038]
[0039] Where: U (j) —The cumulative pass rate corresponding to the jth layer;
[0040] a j —The characteristic parameters of the particle shape of the selected jth layer;
[0041] —The average particle size corresponding to the selected j-th layer of aggregate, that is, the average particle size between layers obtained by formula (1); —The average particle size of the largest interlayer particles selected;
[0042] n—aggregate gradation index, ranging from 0.4 to 0.5.
[0043] Preferably, the specific process of step (3) is:
[0044] 3.1: The type of cementitious material is selected according to the particle size distribution of the Yellow River sand and the optimal particle size range of each cementitious material. The particle size corresponding to the cumulative pass rate of each cementitious material is 50% is smaller than the corrected particle size corresponding to the cumulative pass rate of the Yellow River sand is 50%. It has been measured that the particle size correction coefficient of the Yellow River sand is 1.02-1.06. An air classifier is used to make the particle size distribution of the selected cementitious material meet the requirements; since the particle size of the Yellow River sand is roughly close to that of the cementitious material, the thickness of the water film on its surface cannot be ignored, and the Yellow River sand and cementitious material need to be corrected.
[0045] Preferably, in step 3.1, the so-called optimal particle size range refers to the particle size range in which the gelling material has the highest activity, the best hydration degree and no agglomeration. The optimal particle size ranges of several common gelling materials are shown in Table 1:
[0046] Table 1: Optimal particle size range of common cementitious materials
[0047]
[0048] When the selected cementitious material is not within the optimal particle size range of the cementitious material, that is, the original particle size distribution as a whole does not conform to the optimal particle size range, the selected cementitious material is processed, such as increasing or reducing the particle size by physical and chemical means such as grinding, and the material within the optimal particle size range should account for more than 90% of the total amount, thereby achieving the purpose of improving the utilization rate of raw materials;
[0049] Furthermore, various gelling materials can be classified by an airflow classifier, and each gelling material can be controlled within the optimal particle size range (the optimal particle size range of each gelling material reaches more than 90%) by changing the rotation speed, feeding speed, air intake and other parameters of the classifier.
[0050] 3.2: Pour the selected cementitious materials in step 3.1 into cylindrical molds with a length of 50 mm and a diameter of Φ50 mm, and measure the volume V of various cementitious materials in the dense state and in the dry state. 干 and the volume V in the fully wetted state 湿 , calculate the corresponding particle size correction coefficient λ; the change in force when the crossbeam of the pressure testing machine is displaced per unit Δs is the unit time, Δf is the change in the pressure head force, which means that the material has been pressed to a dense state;
[0051]
[0052] Where: λ-particle size correction coefficient, each gel material corresponds to a particle size correction coefficient λ;
[0053] 3.3: Measure the particle size distribution of each gelling material and obtain the d 10 and d90 , d 10 and d 90 They represent the particle size corresponding to the cumulative percentage of the particle size of the m-th type of cementitious material being 10% and the particle size corresponding to the cumulative percentage of the particle size of the i-th type of cementitious material being 90% respectively;
[0054] The corrected cumulative percentage of composite cementitious materials U is calculated by formula (7): (d) :
[0055] When min ≤d≤d max hour
[0056] where d min - The particle size corresponding to the cumulative percentage of 10% of the i-th type of cementitious material;
[0057] d max - the particle size corresponding to 10% of the cumulative percentage of the cementitious material with a particle size distribution one level higher than that of the i-th cementitious material, or the particle size corresponding to 90% of the cumulative percentage of the cementitious material with the largest particle size distribution interval;
[0058] d i,修正 - Corrected particle diameter of the ith cementitious material, d i,修正 =λ i ·d i ,λ i is the particle size correction coefficient of the i-th cementitious material, d i is the particle size of the i-th cementitious material obtained by testing when the particle size is dry;
[0059] d D,修正 - The corrected particle diameter of the largest cementitious material, d D,修正 =λ D ·d D ,λ D is the correction factor for the particle size of the cementitious material with the largest particle size, d D The particle size of the largest cementitious material when tested dry;
[0060] n-aggregate gradation index, ranging from 0.4 to 0.5;
[0061] The corrected cumulative percentage of composite cementitious materials is obtained as U (d) The relationship between particle size and particle size;
[0062] 3.4: Use a laser particle size analyzer to analyze the particle size curves of each cementitious material and obtain the cumulative passing rate U of the i-th cementitious material in the particle size range m when it is dry. i,m ;
[0063] Assume that the proportion of each cementitious material is p i According to formula (8), the actual passing rate T of composite gelation at particle size d is calculated. d :
[0064] T d =p1·U 1,d +p2·U 2,d …+p n ·U n,d (8)
[0065] Among them, p i - the proportion of the i-th cementitious material,
[0066] U i,d - The i-th cementitious material is in d 湿 Cumulative passing rate at particle size, d 湿 =λ i ·d 干
[0067]
[0068] Among them, R-data fit;
[0069] U (d) -The cumulative percentage of the modified Fuller distribution curve in the jth particle size class is calculated by formula (7);
[0070] Constantly adjust the proportion of each cementitious material i , so that the R value is the smallest. At this time, the calculated curve is closest to the Fuller curve corrected in step 4.3. Finally, the proportion of each cementitious material p is obtained. i .
[0071] Preferably, the process of determining the bone glue ratio in step (4) is:
[0072] According to the specification "Sand for Construction" GB / T 14684-2022, the bulk density of the material, that is, the dry density value, is measured when the mass of sand accounts for 0%, 40%, 70% and 100% of the total mass of the bone glue mixture, and the bone glue ratio corresponding to the maximum bulk density is taken according to the quadratic fitting curve relationship. Specifically: a quadratic fitting is performed on the four sets of data obtained to obtain a quadratic fitting curve. The abscissa is the ratio of the sand mass to the total mass of the bone glue mixture, and the ordinate is the dry density value. The abscissa value corresponding to the maximum dry density of the quadratic fitting curve is taken, that is, the bone glue ratio.
[0073] Preferably, the process of determining the water consumption in step (5) is:
[0074] According to the calculation formula of concrete water-cement ratio:
[0075] W 原 / B 原 =(α a ·f b ) / (f cu,0 +α a α b ·f b ) (10)
[0076] Where: W 原 / B 原 - water-cement ratio of concrete;
[0077] α a , α b - regression coefficient; because the surface of sand particles is smooth, similar to pebbles, α a is 0.49, α b is 0.13;
[0078] f b -28d compressive strength of composite cementitious material;
[0079] f cu,0 - Required concrete mix strength;
[0080] The cementitious materials are mixed according to the proportion designed in step (3), and the water absorption performance test of the cementitious materials other than the cementitious materials that react chemically with water is performed with reference to the volume water absorption test method in GB / T5486-2008 "Test Methods for Inorganic Rigid Thermal Insulation Products" to obtain the unit mass water absorption rate q;
[0081] The corrected water-binder ratio W 新 / B 新 for:
[0082] W 新 / B 新 =(B 原 *p*q+w 原 ) / B 原 (11)
[0083] Where: p-the proportion of cementitious materials that do not react with water to the total cementitious materials;
[0084] q-water absorption per unit mass;
[0085] The corrected water-binder ratio is obtained according to formula (10), and the water consumption is calculated.
[0086] Preferably, step (4) further comprises:
[0087] According to the specification "Test Method for Strength of Cement Mortar" GB / T 17671-2021, the strength under proportion is determined. If the 28d strength is greater than the actual requirement, this parameter is used for design; if it does not meet the requirements, the bone-cement ratio is optimized by reducing the sand content by 3-5% each time, and a strength test is carried out according to the specification until it meets the performance requirements; when the strength is 50% higher than the design strength, considering factors such as economy, the bone-cement ratio is optimized by increasing the sand content by 3-5% each time, and a strength test is carried out according to the specification until it meets the requirements.
[0088] Preferably, the process of determining the static load pressure F in step (6) is:
[0089] Weigh the materials in proportion and mix them, pour them into a cylindrical mold with a length of 50mm and a diameter of Φ50mm, pour them in two layers, shake them after each layer is poured, place the cylindrical mold with the sample on the pressure testing machine, start the pressure testing machine, and apply pressure on one side at a loading speed of 0.01-0.1mm / min until it reaches a dense state, that is, the change in force per unit displacement of the crossbeam of the pressure testing machine Δs is the unit time, Δf is the change in pressure head force, and the corresponding force is the static load pressure F.
[0090] Preferably, in step (3), the proportions of the individual gelling materials are determined, mixed evenly after preparation and stored in a sealed container, and the temperature of the sealed container is controlled at 20+1°C and the relative humidity is <30%.
[0091] Preferably, in step (7), during mixing, the materials that do not chemically react with each other are soaked with one-third of the water used, and cured for 24 to 48 hours in an environment at 20±3°C and a relative humidity of more than 90%, i.e., the materials are stuffed;
[0092] Check the mold size in advance, wipe the mold clean, and evenly apply a thin layer of mineral oil or other isolating agent that does not react with concrete on its inner wall;
[0093] The mixing time and equipment should refer to the regulations. The material temperature should not be higher than 60℃. Mix the stuffed material with the rest of the material. Add the remaining two-thirds of water in 1 to 3 times. Keep the concrete mixture homogeneous during the process.
[0094] During pouring, the concrete mixture is loaded into the mold in layers, and the thickness of each layer is maintained at 5 to 10 cm. After the specimen is formed, the surface is covered with plastic film and allowed to stand for 28 days in an environment with a temperature of 20°C ± 5°C and a relative humidity greater than 50%. After standing, the specimens are numbered and marked, and the molds are removed. During the standing process, water is sprinkled at intervals of 1 to 2 days to keep the surface of the specimens moist.
[0095] Preferably, the mold is in the shape of an elongated strip, and its cross section is in the shape of a rectangle, a diamond, a square, etc., and the side length is 50 cm.
[0096] Where the present invention is not exhaustive, prior art may be used.
[0097] The beneficial effects of the present invention are:
[0098] (1) The flood control stone prepared by the present invention is based on the close packing theory and the thickness and shape of the water film. Since the particle size of the cementitious material changes after being immersed in water, the surface of the aggregate particles is rough, and the shape is irregular, etc., which do not conform to the close packing theory model, a correction coefficient is introduced to improve it so that it is suitable for actual application and reduces the influence of adverse factors. After being manufactured, the properties including strength and durability meet the "Planning, Design and Management Standards for Standardized Levee Engineering in the Lower Yellow River", fully meet the requirements of flood control work, and can be applied to the Yellow River flood control stone embankment project.
[0099] (2) The flood control stone prepared by the present invention has low cost, simple production method, reduced resource waste, no environmental pollution, is convenient for factory production, and is easy to promote and apply.
[0100] (3) The flood control stones prepared by the present invention have regular shapes and are easy to transport, arrange, and throw, which greatly reduces the labor intensity of operators and greatly improves operating efficiency.
[0101] (4) The flood control stone prepared by the present invention is made of local materials, has high material utilization rate, is pollution-free during use, and is suitable for wide use. BRIEF DESCRIPTION OF THE DRAWINGS
[0102] Figure 1 is the force-displacement relationship diagram;
[0103] Figure 2 This is a comparison chart of the Fuller curve before and after;
[0104] Figure 3 The cross-section diagram of the flood control stone, where (a) to (d) are the corresponding four shapes;
[0105] Figure 4 The particle size distribution of Yellow River sand obtained by laser particle size analyzer;
[0106] Figure 5 This is a force-time relationship diagram. DETAILED DESCRIPTION
[0107] In order to make the technical problems, technical solutions and advantages to be solved by the present invention more clear, they will be described in detail with reference to the accompanying drawings and specific embodiments, but are not limited to these. Anything not fully described in the present invention shall be based on conventional techniques in the art.
[0108] Example
[0109] A design and preparation method of Yellow River sand flood control stone based on water film thickness and shape correction, comprising the following steps:
[0110] (1) Sorting and drying of Yellow River sand, and particle size analysis of Yellow River sand using a laser particle size analyzer
[0111] The wood, plastic products, large stones and other debris in the Yellow River sand were manually sorted and removed, and then dried in a dryer at a temperature of 60-100°C. The particle size distribution was obtained by laser particle size analyzer. Figure 4 As shown (D10 = 17.33 μm, D50 = 46.81 μm, D90 = 104.0 μm respectively represent the particle sizes when the cumulative passing rate is 10%, 50% and 90%);
[0112] (2) Based on the particle size analysis of aggregates, the shape characteristic parameters are tested, the proportion of aggregates is determined, and mixed and sealed.
[0113] 2.1: Based on the particle size analysis results of Yellow River sand, the particle size with a cumulative pass rate of 50% is 46.81μm, which is r. The aggregate particle size range is 0.07-0.404mm. The particle sizes required between layers from top to bottom are 0.40mm, 0.17mm, 0.09mm and 0.07mm (corresponding to 8.62r, 3.57r, 1.94r and 1.52r);
[0114] The mesh size settings from top to bottom are shown in Table 2. The average particle size of the interlayer particles Calculate according to formula 1;
[0115] Table 2: Summary of average particle size of aggregates at various levels of screening
[0116]
[0117] 2.2: Test the roundness and aspect ratio of the particles between each layer and calculate the particle shape characteristic parameters according to formula (2). The results are shown in Table 3
[0118] Table 3: Summary of aspect ratio and roundness of aggregates of different particle sizes
[0119]
[0120] In Table 3, since 0.256 mm is not close to the above 0.40 mm, 0.17 mm, 0.09 mm, and 0.07 mm, it is not necessary to calculate the shape characteristic parameters of 0.256 mm;
[0121] 2.3: According to formula (5), the aggregate gradation index is taken as 0.4, and the dosage of particles of each average particle size is calculated and determined as shown in Table 4;
[0122] Table 4: Summary of determination of particle size ratios
[0123]
[0124] In Table 4, the original Fuller curve calculation formula for the cumulative pass rate is:
[0125]
[0126] Compared with the revised formula, which lacks the particle shape parameter, the cumulative passing rate can be obtained by substituting it into this formula;
[0127] Taking 0.070mm particles as an example, the dosage calculation process is 48.61-41.45=7.16, and so on.
[0128] Taking the average particle size of 0.159 mm as an example, the calculation process is:
[0129] The original Fuller curve calculates the cumulative pass rate (%):
[0130]
[0131] Original dosage (%):
[0132] 67.48-54.45=13.03%;
[0133] Modified Fuller curve calculation cumulative pass rate (%):
[0134]
[0135] Corrected dosage (%):
[0136] 85.38-72.29=13.10
[0137] Figure 2 This is a comparison chart of the Fuller curve before and after;
[0138] Refer to GB / T 14684-2022 "Construction Sand" for the test bulk density results, see Table 5:
[0139] Table 5: Summary of aggregate bulk density
[0140]
[0141] The values in Table 5 are obtained based on the bulk density experiment in the specification; Table 5 can verify that the revised formula has a good application effect. 0.047 :m 0.070 :m 0.093 :m 0.159 :m 0.425 (Yellow River sand) = 52.90:13.83:5.56:13.12:14.58, and mix evenly to make new aggregate and seal it.
[0142] (3) Select the type of cementitious material, modify the particle size, determine the cementitious material ratio, and mix and seal it
[0143] 3.1: Taking the particle size correction coefficient of Yellow River sand as 1.03, the corrected particle size of the Yellow River sand with a cumulative passing rate of 50% is 48.21μm. According to Table 1, the types of cementitious materials are selected as follows: fluidized bed fly ash (24-58μm), silicate cement (8μm-24μm), and high calcium powder (<8μm);
[0144] Fluidized bed fly ash, silicate cement and high calcium powder are passed through a controlled classifier to make their particle size distribution concentrated. The parameters are shown in Table 6:
[0145] Table 6: Classifier parameters
[0146]
[0147] The particle size analysis was performed, and the results are shown in Table 7:
[0148] Table 7: Summary of particle size distribution information of three cementitious materials
[0149]
[0150] 3.2: Pour the silicate cement, high calcium powder and fluidized bed fly ash in step 3.1 into a cylindrical mold with a length of 50 mm and a diameter of Φ50 mm, and measure the volume V of each cementitious material in the dense state when it is dry. 干 and the volume V in the fully wetted state 湿 , calculate the corresponding particle size correction coefficient λ according to formula (6):
[0151] See Table 8 for relevant parameters:
[0152] Table 8: Calculation table of correction factor λ of cementitious materials
[0153]
[0154] 3.3: The corrected cumulative percentage of composite cementitious materials is calculated by formula (7). The corrected Fuller formula is:
[0155] When 1.3<d<8.6μm,
[0156] Note: d 1,修正 -Diameter of wet high calcium powder particles;
[0157] d1- diameter of dry high calcium powder particles;
[0158] d D,修正 - Maximum diameter of wet fluidized bed fly ash particles;
[0159] d D -The maximum diameter of the dry fluidized bed fly ash particles is 57.2 μm, which corresponds to a cumulative pass rate of 90%;
[0160] λ1——Correction coefficient of high calcium powder, which is 1.05 according to Table 8;
[0161] λ D ——Correction coefficient for fluidized bed fly ash: 1.21 according to Table 8;
[0162] When 8.6μm<d<25.3μm,
[0163] d 2,修正 - diameter of wet Portland cement particles;
[0164] d2-diameter of dry Portland cement particles;
[0165] λ2- correction factor of silicate cement, according to Table 8, it is 1.17;
[0166] When 25.3μm<d<57.2μm,
[0167] d 3,修正 - diameter of wet fluidized bed fly ash particles;
[0168] d3 - diameter of dry fluidized bed fly ash particles;
[0169] In summary:
[0170] The function corresponding to the final particle size distribution is:
[0171] When 1.3<d<8.6μm,
[0172] When 8.6μm<d<25.3μm
[0173] When 25.3μm<d<57.2μm,
[0174] 3.4: The particle size curves of various gelling materials under dry conditions were analyzed using a laser particle size analyzer. The results are shown in Table 9 below:
[0175] Table 9: Cumulative pass rate of a single cementitious material within the particle size range of m
[0176]
[0177] Assuming that the mass proportions of fluidized bed fly ash, cement and high calcium powder in cementitious materials are p1, p2 and p3 respectively, then:
[0178] p1+p2+p3=1
[0179] T d =p1·U 1,d +p2·U 2,d +p3·U 3,d
[0180] Where: U 1,d , U 2,d and U 3,d They are the passing rates of high calcium mineral powder, silicate cement and fluidized bed fly ash in grade D respectively.
[0181] Constantly adjust the proportion of each cementitious material i , so that the R value is the smallest. At this time, the calculated curve is most similar to the Fuller curve corrected in step 3.3. In this embodiment, the final R is 338, and the corresponding p1:p2:p3=0.37:0.11:0.52. At this time, the actual curve is closest to the corrected Fuller curve, and the tight stacking effect is the best.
[0182] That is, this step determines that the mass ratio of the composite cementitious material composition is fluidized bed fly ash: silicate cement: high calcium powder = 0.37: 0.11: 0.52, wherein the particle size range of the fluidized bed fly ash is 24 to 58 μm, the particle size range of the silicate cement is 8 μm to 24 μm, and the particle size range of the high calcium powder is 0 to 8 μm.
[0183] Determine the proportion of each single gelling material, mix them evenly after preparation and store them in a sealed container. Control the temperature of the sealed container to 20+1°C and the relative humidity to <30%.
[0184] (4) Determine the bone glue ratio, the process is as follows:
[0185] According to the specification "Construction Sand" GB / T 14684-2022, the bulk density of the material when the mass of sand accounts for 0%, 40%, 70% and 100% of the total mass of the gelatin mixture is measured, that is, the dry density value, see Table 10:
[0186] Table 10: Dry density of mixed materials in different proportions
[0187]
[0188]
[0189] Performing quadratic fitting on the four sets of data, we get the functional relationship: y1 = -1.3283x 2+1.9233x+1.0419, the x value corresponding to the maximum dry density of the quadratic curve is calculated, which corresponds to x1=0.73 in this embodiment. The sand content is tentatively set to 73%, and the mass of sand and composite cementitious material is 73:27. According to the specification "Test Method for Strength of Cement Mortar" GB / T 17671-2021, the 28d mortar strength under this bone-cement ratio is 9.6MPa, which meets the requirements.
[0190] (5) Determine the water-cement ratio by referring to the specification and make corrections based on the actual water absorption characteristics of the material to determine the water consumption
[0191] The process for determining water usage is:
[0192] According to formula (10), the water-binder ratio W is calculated. 原 / B 原 =0.48, where the parameters are as follows α a is 0.49, α b is 0.13, f b is 9.6MPa, f cu,0 5MPa;
[0193] The new water-binder ratio is calculated to be 0.53 according to formula (11), where the parameters are as follows: 原 =0.48B 原 , p is 0.89, q is 0.06;
[0194] The final material mass ratio is:
[0195] m 高钙粉 ∶m 硅酸盐水泥 ∶m 流化床粉煤灰 ∶m 骨料 ∶m 水 =0.52∶0.11∶0.37∶2.7∶0.53.
[0196] (6) Determine the static load pressure F;
[0197] Weigh the materials in proportion and mix them, pour them into a cylindrical mold with a length of 50mm and a diameter of Φ50mm, pour them in two layers, shake them after each layer, place the cylindrical mold with the sample on the pressure testing machine, start the pressure testing machine, and apply pressure on one side at a loading speed of 0.01~0.1mm / min until it reaches a dense state. Analysis of the experimental data shows that the pressure range is 507.635N~510.2N, corresponding to Figure 1 F1 and F2, take 510N as the static load pressure F, the experimental results are as follows Figure 5 shown.
[0198] (7) Mix and pour into a mold for shaping and curing.
[0199] Soak the materials that do not react chemically with each other with one third of the water used, and cure them for 24 to 48 hours in an environment of 20±3℃ and relative humidity above 90%;
[0200] Check the mold size in advance, wipe the mold clean, and evenly apply a thin layer of mineral oil or other isolating agent that does not react with concrete on its inner wall;
[0201] The mixing time and equipment should refer to the regulations. The material temperature should not be higher than 60℃. Mix the stuffed material with the rest of the material. Add the remaining two-thirds of water in 1 to 3 times. Keep the concrete mixture homogeneous during the process.
[0202] During pouring, the concrete mixture is loaded into the mold in layers. Figure 3 As shown in (a) to (d), the loading thickness of each layer is maintained at 5 to 10 cm. After the specimen is formed, the surface is covered with plastic film and allowed to stand for 28 days in an environment with a temperature of 20°C ± 5°C and a relative humidity greater than 50%. After standing, the specimen is numbered and marked, and the mold is removed. During the standing process, water is sprinkled at intervals of 1 to 2 days to keep the surface of the specimen moist and maintain the molding.
[0203] The compression resistance, weathering resistance and freeze-thaw resistance properties tested in accordance with relevant specifications are as follows:
[0204] Table 11: Compression performance of P-CFB specimens
[0205]
[0206] In P-CFB, P refers to cement, and CFB refers to fluidized bed fly ash, i.e., the specimen made in this embodiment;
[0207] According to the reference specification "Geotechnical Test Specification", the 28d strength must be greater than 5MPa, which obviously meets the specification requirements.
[0208] Table 12: Weathering resistance of specimens
[0209]
[0210] According to the specification "Sintered Ordinary Bricks" (GB5101-2003), the single value of the boiling water absorption for 5h is not more than 25%, the average value is not more than 23%, the single value of the saturation coefficient is not more than 0.9, and the average value is not more than 0.88. In this embodiment, the single value of the boiling water absorption for 5h is less than 25%, the average value is 7.78% and not more than 23%, the single value of the saturation coefficient is not more than 0.9, and the average value is 0.2 and not more than 0.88. Obviously, the prepared specimens meet the requirements of weathering resistance.
[0211] Table 13: Freeze-thaw performance
[0212]
[0213]
[0214]
[0215]
[0216] According to the specification "Test Methods for Basic Properties of Building Mortar": When the compressive strength loss rate of the freeze-thaw specimens is not more than 25%, and the mass loss rate is not more than 5%, the frost resistance of this group of specimens is qualified under the number of test cycles, otherwise it is unqualified. Obviously, the prepared specimens meet the frost resistance requirements.
[0217] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing Yellow River sand flood control stones based on water film thickness and shape correction, characterized in that: The steps include: (1) Sorting and drying the Yellow River sand, and analyzing the particle size of the Yellow River sand using a laser particle size analyzer; (2) Based on the particle size analysis of aggregates, the shape characteristic parameters are tested, the proportion of aggregates is determined, and the aggregates are mixed and sealed; (3) Select the type of cementitious material, modify the particle size, determine the proportion of cementitious materials, mix and seal; (4) Determine the bone-gel ratio; (5) Determine the water-cement ratio by referring to the specifications and make corrections based on the actual water absorption characteristics of the material to determine the amount of water used; (6) Determine the static load pressure F; (7) Mixing, pouring into a mold, and curing; The process of determining the proportion of aggregate in step (2) is as follows: 2.1: Based on the particle size analysis of Yellow River sand, since the particle size distribution of Yellow River sand is concentrated, the particle size with a cumulative pass rate of 50% can be set as r to represent the average particle size of Yellow River sand. The aggregate particle size range is selected to be 1.52r~8.62r. According to the interlayer particle size required by the Horsfield stacking model, the upper and lower interlayer sieve aperture sizes are determined. From top to bottom, the required particle sizes between the layers are 8.62r, 3.57r, 1.94r and 1.52r. The difference in the mesh size of the upper and lower sieves is less than 0.3mm. Since the upper and lower aperture sizes are close, the average particle size of each interlayer particle is calculated according to formula (1): Where: —average particle size between layers i; —The aperture size of the upper screen; —Aperture size of the lower screen: 2.2: Test the roundness and aspect ratio of particles between each layer. Roundness refers to the degree to which particles are close to a circle. The lower the roundness value, the closer the particles are to a circle. When the slump is the same, the lower the shape characteristic parameter, the smaller the interlocking effect between particles, the smaller the porosity of the mixture, and the higher the packing density. a i =R×Q (2) Where: a i — characteristic parameters of particle shape in layer i; R—particle roundness; Q—aspect ratio; in, Where: R—particle roundness; P—the circumference of the particle under the scanning electron microscope; area—the area of the particle projection under the scanning electron microscope; The aspect ratio is the ratio of the length and width of the particle diameter. The aspect ratio is: Where: Q—aspect ratio; L—particle length under scanning electron microscope; W—particle width under scanning electron microscope; 2.3: Calculate the cumulative passing rate corresponding to the selected particle size by referring to the modified Fuller distribution curve (Formula 5), and determine the dosage of the selected interlayer particles, that is, the proportion of the interlayer particles of the final selected aggregate; Where: U (j) —The cumulative pass rate corresponding to the jth layer; a j —The characteristic parameters of the particle shape of the selected jth layer; —The average particle size corresponding to the selected j-th layer of aggregate, that is, the average particle size between layers obtained by formula (1); —The average particle size of the largest interlayer particles selected; n—aggregate gradation index, ranging from 0.4 to 0.5; The specific process of step (3) is as follows: 3.1: Select the type of cementitious material based on the particle size distribution of Yellow River sand and the optimal particle size range of each cementitious material; 3.2: Pour the selected cementitious materials in step 3.1 into cylindrical molds with a length of 50 mm and a diameter of Φ50 mm, and measure the volume V of various cementitious materials in the dense state and in the dry state. 干 and the volume V in the fully wetted state 湿 , calculate the corresponding particle size correction coefficient λ; the change in force when the crossbeam of the pressure testing machine is displaced per unit Δs is the unit time, Δf is the change in the pressure head force, which means that the material has been pressed to a dense state; Where: λ—particle size correction coefficient, each gel material corresponds to a particle size correction coefficient λ; 3.3: Measure the particle size distribution of each gelling material and obtain the d 10 and d 90 , d 10 and d 90 They represent the particle size corresponding to the cumulative percentage of the particle size of the m-th type of cementitious material being 10% and the particle size corresponding to the cumulative percentage of the particle size of the i-th type of cementitious material being 90% respectively; The corrected cumulative percentage of composite cementitious materials U is calculated by formula (7): (d) : When min ≤d≤d max hour where d min —The particle size corresponding to the cumulative percentage of 10% of the i-th type of cementitious material; d max —the particle size corresponding to 10% of the cumulative percentage of the cementitious material with a particle size distribution one level higher than that of the i-th cementitious material, or the particle size corresponding to 90% of the cumulative percentage of the cementitious material with the largest particle size distribution interval; d i , 修正 —The corrected particle diameter of the i-th cementitious material, d i , 修正 =λ i ·d i ,λ i is the particle size correction coefficient of the i-th cementitious material, d i is the particle size of the i-th cementitious material obtained by testing when the particle size is dry; d D , 修正 —The corrected particle diameter of the largest cementitious material, d D , 修正 =λ D ·d D ,λ D is the correction factor for the particle size of the cementitious material with the largest particle size, d D The particle size of the largest cementitious material when tested dry; n—aggregate gradation index, ranging from 0.4 to 0.5; The corrected cumulative percentage of composite cementitious materials is obtained as U (d) The relationship between particle size and particle size; 3.4: Use a laser particle size analyzer to analyze the particle size curves of each cementitious material and obtain the cumulative passing rate U of the i-th cementitious material in the particle size range m when it is dry. i , m ; Assume that the proportion of each cementitious material is p i According to formula (8), the actual passing rate T of composite gelation at particle size d is calculated. d : T d =p1·U1, d +p2·U2, d …+p n ·U n , d (8) Among them, p i —the proportion of the i-th cementitious material, U i , d —The i-th cementitious material is in d 湿 Cumulative passing rate at particle size, d 湿 =λ i ·d 干 Among them, R—data fit; U (d) —The cumulative percentage of the modified Fuller distribution curve in the jth particle size class, calculated by formula (7); Constantly adjust the proportion of each cementitious material i , so that the R value is the smallest. At this time, the calculated curve is closest to the Fuller curve corrected in step 3.
3. Finally, the proportion of each cementitious material p is obtained. i ; The process of determining water consumption in step (5) is as follows: According to the calculation formula of concrete water-cement ratio: W 原 / B 原 =(a a ·f b ) / (f cu ,0+a a ·a b ·f b ) (10) Where: W 原 / B 原 — water-cement ratio of concrete; α a ,α b —Regression coefficient; Since the surface of sand particles is smooth, similar to pebbles, α a is 0.49, α b is 0.13; f b —28d compressive strength of composite cementitious material; f cu , 0—required mix strength of concrete; Since fluidized bed fly ash and high calcium powder have strong water absorption, water absorption performance tests were carried out to determine the water absorption performance of W 原 / B 原 Make corrections, the correction process is: The cementitious materials are mixed according to the proportion designed in step (3), and the water absorption performance test of the cementitious materials other than the cementitious materials that react chemically with water is performed with reference to the volume water absorption test method in GB / T5486-2008 "Test Methods for Inorganic Rigid Thermal Insulation Products" to obtain the unit mass water absorption rate q; The corrected water-binder ratio W 新 / B 新 for: W 新 / B 新 =(B 原 *p*q+w 原 ) / B 原 (11) Where: p is the proportion of cementitious materials that do not react with water to the total cementitious materials; q—water absorption per unit mass; The corrected water-binder ratio is obtained according to formula (10), and the water consumption is calculated.
2. The method for preparing Yellow River sand flood control stone based on water film thickness and shape correction according to claim 1, characterized in that the process of determining the bone glue ratio in step (4) is: The bulk density of the material, i.e., the dry density value, was measured when the mass of sand accounted for 0%, 40%, 70% and 100% of the total mass of the gelatin mixture, respectively. A quadratic fit was performed based on the four sets of data to obtain a quadratic fitting curve, in which the abscissa was the ratio of the mass of sand to the total mass of the gelatin mixture, and the ordinate was the dry density value. The abscissa value corresponding to the maximum dry density of the quadratic fitting curve was taken, i.e., the gelatin ratio.
3. The method for preparing Yellow River sand flood control stones based on water film thickness and shape correction according to claim 2, characterized in that step (4) also includes: Measure the strength under proportion. If the 28d strength is greater than the actual requirement, use this parameter for design. If it does not meet the requirements, optimize the bone-cement ratio by reducing the sand content by 3-5% each time, and conduct strength tests according to the specifications until it meets the performance requirements. When the strength is 50% higher than the design strength, consider economic factors, optimize the bone-cement ratio by increasing the sand content by 3-5% each time, and conduct strength tests according to the specifications until it meets the requirements.
4. The method for preparing Yellow River sand flood control stones based on water film thickness and shape correction according to claim 3 is characterized in that: The process of determining the static load pressure F in step (6) is as follows: Weigh the materials in proportion and mix them, pour them into a cylindrical mold with a length of 50mm and a diameter of Φ50mm, pour them in two layers, shake them after each layer is poured, place the cylindrical mold with the sample on the pressure testing machine, start the pressure testing machine, and apply pressure on one side at a loading speed of 0.01-0.1mm / min until it reaches a dense state, that is, the change in force per unit displacement of the crossbeam of the pressure testing machine Δs is the unit time, Δf is the change in pressure head force, and the corresponding force is the static load pressure F.
5. The method for preparing Yellow River sand flood control stone based on water film thickness and shape correction according to claim 4 is characterized in that: In step (3), the proportions of the individual gelling materials are determined, mixed evenly after preparation and stored in a sealed container, and the temperature of the sealed container is controlled at 20±1° C. and the relative humidity is <30%.
6. The method for preparing Yellow River sand flood control stone based on water film thickness and shape correction according to claim 5, characterized in that: In step (7), during mixing, the materials that do not chemically react with each other are soaked with one third of the water used, and cured for 24 to 48 hours in an environment of 20±3° C. and a relative humidity of more than 90%, i.e., the materials are stuffed; Check the mold size in advance, wipe the mold clean, and evenly apply a thin layer of mineral oil or other isolating agent that does not react with concrete on its inner wall; The mixing time and equipment should refer to the regulations. The material temperature should not be higher than 60℃. Mix the stuffed material with the rest of the material. Add the remaining two-thirds of water in 1 to 3 times. Keep the concrete mixture homogeneous during the process. During pouring, the concrete mixture is loaded into the mold in layers, and the thickness of each layer is kept at 5 to 10 cm. After the specimen is formed, the surface is covered with plastic film and allowed to stand for 28 days in an environment with a temperature of 20℃±5℃ and a relative humidity greater than 50%. After standing, the specimens are numbered and marked, and the molds are removed. During the standing process, water is sprinkled at intervals of 1 to 2 days to keep the surface of the specimens moist.
7. The method for preparing Yellow River sand flood control stone based on water film thickness and shape correction according to claim 6, characterized in that: The mold is in the shape of a long strip, and its cross section is rectangular, rhombus or square, and the side length is 50 cm.
Citation Information
Patent Citations
Design method for mixing proportion of self-compacting concrete mixture
CN105224727A
Mix composition determination method of coarse graded high modulus asphalt concrete with skeleton embedded structure
US20140245925A1